Legal Protection for Parties in Sale and Purchase Transactions of Virtual Objects - Arzetta Zahra Metthania; Siti Nurul Intan Sari Dalimunthe (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
This study aimed to analyze the regulation concerning transactions of buying and selling virtual objects in Indonesia and find out the legal protection for the parties in the event of default in such transactions. This study was normative juridical research using secondary data and statute approach. Virtual objects are intangible objects that, referring to Article 499 of the Civil Code, can be claimed, can be of property rights, and have economic value. The regulation concerning transactions for virtual objects refers to arrangement of buying and selling transactions in the Civil Code, specifically in Articles 1457 to Article 1540 there of. Legal protection for the parties in buying and selling virtual objects refers to the agreement made by the parties. However, in buying and selling virtual objects, there is no written agreement except an agreement made based on conversations via social media of the parties, such as WhatsApp or E-mail. Therefore, any default committed by either party can only be proven by the provisions made by the parties in their conversations. On this matter, referring to Law No. 8 of 1999 concerning Consumer Protection, business actors are entitled to receive payments or goods, while the consumers are entitled to receive compensation if the goods received are not in accordance with the agreement.